Legal Challenges of Digital Platform Operators in the Context of the Privacy Paradox - Dimović, Zoran (Digital Platforms: Legal And Economic Challenges, 2024)
The digital industry has long driven the growth of platforms that dominate market share, a trend expected to continue. The shift to mobile and digital environments exposes individuals to sharing personal data. The Digital Markets Act outlines key responsibilities for platform operators, particularly regarding access to personal data, requiring platforms to provide business users with free access. This article explores the privacy paradox, focusing on the balance between digital convenience and the right to privacy, and examines the challenges faced by platform operators in balancing innovation with data protection.